Efeito dos níveis de cantaxantina na dieta sobre o desempenho e qualidade dos ovos de poedeiras comerciais - Garcia, E. A. [UNESP]; Mendes, A. A. [UNESP]; Pizzolante, C. C. [UNESP]; Gonçalves, H. C. [UNESP]; Oliveira, R. P. [UNESP]; Silva, Ma [UNESP] (My University, 2002)
The objective of this study was to evaluate the effects of cantaxantina levels on performance and egg yolk color. Three hundred and eighty four Hisex laying 65-week old hens were randomized allocated in a block design with six treatments (0, 12, 24, 26, 48 and 60 ppm of cantaxantina, and eight replications of eight birds per pen, during eight weeks. The egg color analysis was determined using the Roche fan colorimeter. The best egg yolk color (14.3) during the first 14 days of essay were reached at 5.43 days of receiving diets with 60 ppm of cataxantina. During the total period, egg yolk color increased quadratically (p<.05) as cataxantina level increased, while egg production, egg weight, feed consumption, feed conversion, yolk and albumen percentage and shell thickness were not affected by treatments (p>.05).
Effect of cantaxantina levels on performance and egg quality of laying hens
Keywords: Egg quality; Laying hens; Performance; Pigments; Yolk color